The Short-Run Impact of fluctuating primary commodity prices on three developing economies: Colombia, Ivory Coast and Kenya - Hermann Dick; Sanjeev Gupta; Thomas Mayer; David P. Vincent (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1982)
Computable general equilibrium models are used to study the short-run impact of fluctuating primary commodity prices on the economies of Colombia, Ivory Coast and Kenya. The results indicate that these economies are destabilized by primary commodity price fluctuations unless governments act to hold real domestic absorption constant. To achieve this, however, would require foreign exchange reserves in excess of the level normally available to these governments for the purpose of stabilising, domestic economic activity.
Keywords: 330